RIGHTS OF WOMEN DURING PRE-MARRIAGE FROM QURâ€™ANIC PERSPECTIVES WITH CROSS-REFERENCE TO THE LAW IN MALAYSIA: AN ANALYSIS - Nadzrah Ahmad; Rahmawati Mohd Yusoff; Mohammad Hidir Baharudin (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Womenâ€™s rights issues have marked their spot as one of the most debated issues throughout the centuries. Whenever the issue is raised, the topic of marriage is the most highlighted concerning the discussion. Marriage is regularly portrayed as an â€œoppressive sphereâ€ for women, with their rights being oppressed since the moment of pre-marriage, especially in Islam. However, further reflection on the issue has shown that Islamic matrimony liberates women, preserves their honour and place in society, and abolishes injustice when guided in principle from the Qurâ€™an and the Sunnah of Prophet Muhammad (PBUH) which will be examined in this research. The paper will also analyse the issue in the law of Malaysia and supported by the case law if any. In addition, reference will also be made to the opinions of the scholars regarding the conflicting issue of the rights of women during pre-marriage. Regrettably, Muslimsâ€™ misunderstanding due to cultural interpretation and mispractice of original Islamic teachings have tainted the true Islamic ideal. It is hoped that the study may provide a clear reference and guideline regarding the rights of women during pre-marriage from both the Islamic and Malaysian laws as this topic is highly significant and beneficial to numerous parties in the present day.